Pengaruh Corporate Social Responsibility Disclosure, Quick Ratio, Debt To Equity Ratio, Return On Asset, Dan Net Profit Margin Terhadap Nilai Perusahaan - Lilik Mardiana (LPPM Universitas Wijaya Kusuma Surabaya, 2024)
The aims of this research to examine and analyze the effect of the disclosure of Corporate Social Responsibility Disclosure, Quick Ratio, Debt to Equity Ratio, Return on Assets, and the Net Profit Margin against the value of the company which is proxied by Tobin's Q. The objects used in this research are manufacturing companies listed on the Stock Exchange during the study period 2012-2014. The analysis technique used in this study is multiple regression analysis. This research uses a quantitative approach. In determining the sample used purposive sampling method. By using this method, acquired 53 manufacturing companies that meet the criteria of this research. The result of research, simultaneous shows that CSR, Quick Ratio, DER, ROA, and NPM significantly affects the value of the company. In partial CSR, DER, ROA, and the NPM significantly affects the value of the company, Quik Ratio whereas no significant effect on the value of the company.